Comparison of Lip Print Patterns in Two Indian Subpopulations and Its Correlation in ABO Blood Groups - SR, Ashwinirani (J Clin Diagn Res, 2014)
Background: The study of lip-print pattern (cheiloscopy) is a scientific method for personal identification and plays a major role in forensic and criminal investigations. Objective: To compare the lip print patterns in Kerala and Maharashtra population and correlate between ABO blood groups. Materials and Methods: Two hundred subjects, 100 from Maharashtra and 100 from Kerala were considered for the study. Lip prints were recorded, analyzed according to Tsuchihashi classification. The lip print patterns were compared in the two populations, correlated in ABO blood groups. The data obtained was statistically analyzed with SPSS software using chi-square test. Results: In our study, predominant lip print pattern observed in Kerala population was type IV (53%) and Maharashtra population was type II (42%). The difference between the two population was statistically significant (p<0.001). Subjects with A+ and O- blood groups had type II lip print predominance. Subjects with B+, AB+ and O+ blood groups had type IV predominance. The lip print patterns do not show any correlation in ABO blood groups. Conclusion: Lip prints are unique to each individual and are different even in two persons. Lip print patterns were different in the two sub populations studied, and they showed no correlation in ABO blood groups.